Intervensi Psikoedukasi "Anti Miras" : Peran Penguatan Peran Tokoh Masyarakat Untuk Pencegahan Minuman Keras - Ema Zati Baroroh; Wisnu Sri Hertinjung (JIP (Jurnal Intervensi Psikologi), 2017)
The decrease in the role of community leaders and religious leaders in overcoming alcoholic irregularities is  a separate problem in a community community. The purpose of this research is generally to increase the knowledge of community and religious leaders in the prevention of misuse of alcoholic irregularities. The hypothesis of this study is that the knowledge on MIRAS on the subject would be found higher or increased after obtaining psychoeducation "Anti MIRAS". The participants of this study were community leaders and religious leaders who stated their agreement and willingness. Data were analyzed by Paired Sample of T-Test and qualitatively. Quantitative results indicate that psychoeducation intervention "Anti MIRAS" did not significantly increase participants' knowledge. However, the qualitative results found that the outcome of this intervention was able to provide a positive insight about the dangers of MIRAS and bridging communityleaders to agree on 11 points of agreement. Findings, limitations and recommendations in this study will alsobe discussed.Keywords: Alcohol abuse, Empowerment, Community, Psycho-education